Monday Club building invoice, Julia Morgan and J. Jepson, payment 6 (1934)
Payments to James J. Jepson, San Luis Mill & Lumber Co., Sandercock Transfer Co., Union Hardware & Plumbing Co., and H.G. Klaucke, C.H. Reed Company.